Perkembangan Perekonomian Syariah di Indonesia, Dampak Reformasi Industri Halal - Saddam Hatta Leondy; Zakky Darmawan; Adi Apriliyanto; Muhammad Zaki Zamani (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2024)
The increase in Indonesia's position in SGIE to 3rd place in 2023, raises several challenges faced such as the awareness of the Indonesian people regarding the halal industry and the regulations regarding the free halal certification program (SEHATI). The purpose of writing this research is to analyze how government regulations can play an important role in producing a good program. In addition, public awareness of the SEHATI program can also increase the effectiveness of the program. Researchers used a descriptive qualitative approach method. The research stages carried out begin with problem identification, making questions related to the problem, interviewing and distributing questionnaires, analyzing research results, evaluation. The results of this study found that. However, the majority of MSMEs strongly support the SEHATI program and also regulations that require MSMEs to obtain halal certification have received a positive response, indicated by the high awareness of MSMEs regarding compliance with applicable rules and regulations, but regulations related to the SEHATI program are still ineffective as seen from the many complaints from PPH Facilitators regarding the regulations and systems of the SEHATI program.